Perbedaan tingkat stres sebelum dan sesudah senam jantung sehat pada lansia di Panti Sosial Tresna Werdha Sinta Rangkang Palangka Raya - Hartoyo, Riccardo; Kahanjak , Donna Novina; Nugrahini , Sintha; Balyas , Abi Bakring; Mutiasari , Dian (Barigas: Jurnal Riset Mahasiswa, 2024)
Stress is the body's response to stressors. The prevalence of stress in the elderly undergoing care at social care homes reaches 30%. Stress can be managed with non-pharmacological therapies such as exercise, one of which is healthy heart gymnastics. This study aims to determine the difference in stress levels before and after performing healthy heart gymnastics in the elderly at the Tresna Werdha Sinta Social Care Home in Palangka Raya. This research is a quasi-experimental study with a one-group pre-test post-test design. Sampling was done using purposive sampling technique with a total of 23 samples. The study was conducted for 2 weeks, and the healthy heart gymnastics intervention was given twice a week. Bivariate data analysis was performed using the Wilcoxon test. The percentage of normal stress levels in the pre-test and post-test categories increased from 78.3% to 95.7%. The results of the statistical analysis showed a significant difference in stress levels before and after healthy heart gymnastics in the elderly at the Tresna Werdha Sinta Social Care Home in Palangka Raya with a p-value = 0.025. Healthy heart gymnastics indicates a positive impact on stress levels in the elderly at the Tresna Werdha Sinta Social Care Home in Palangka Raya.